A DFT study of nonlinear optical response of supersalt (Al(BH4)3) doped boron nitride. Issue 1 (31st December 2022) - Bano, Nigarish; Bhatti, Ijaz Ahmad; ul-Ain, Qurat; Mohsin, Muhammad; Shehzad, Rao Aqil; Iqbal, Javed
Abstract : In the current study, optical and nonlinear optical (NLO) properties of supersalt Al(BH4 )3 doped boron nitride (BN) were studied by employing density functional theory (DFT) at the MPW1PW91/6-31 G (d, p) level of theory. HOMO–LUMO energy gap of 7.48 eV was found for pure BN which is reduced to 4.85 eV after doping. Supersalt doping has shown better results on the NLO properties including a decrease in the excitation energy, change in vertical ionization energies, increase in oscillator strength, and increase in dipole moment. Doped molecules have lesser transition energies (ΔE) that lead to higher hyperpolarizability. Electron density difference map was plotted which describes the distribution of electrons of doped compounds. The enhanced values of αiso and βstatic are observed which increases the NLO properties. Overall, the results have shown that supersalt doped boron nitride is an effective approach for designing efficient nonlinear material.